Meningkatkan Hasil Belajar Pak Melalui PBL Berbantuan PPT di SDN 091450 Bah Tongguran - Rosmauli Sitohang (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
Education plays an important role in preparing qualified and competent workforce, and becomes a benchmark for a country's development. The quality of the teaching and learning process in schools is greatly influenced by students' learning motivation and teacher creativity. However, Catholic Religious Education learning at SDN 091450 Bah Tongguran often faces challenges, such as monotonous teaching methods, which cause a lack of student interest. This study aims to improve student activity and learning outcomes through the application of the Project Based Learning Model (PBL). This research method involves grade III students with a focus on increasing learning activities and self-understanding as developing individuals. The results of the study indicate that the application of the technology-assisted PBL model can improve motivation and learning outcomes, as reflected in the increase in average scores from cycle I to cycle II, as well as improvements in student character indicators. These findings confirm that the PBL method has the potential to improve the effectiveness of Catholic Religious Education learning, and it is recommended for teachers to use this method to create a more interactive and enjoyable learning environment.